Сучасні запатентовані способи переробки посліду птахів - Комар, Артем Станіславович; Комар, Артем Станиславович; Komar, Artem (My University, 2021)
UK: В статті наведено сучасні способи та технології переробки посліду птахів. Кожна з наведених технологій має видимі та приховані недоліки. Відходи птахівництва використовуються неекологічно і нераціонально при зберіганні в сховищах для посліду, сушінні посліду різної вологості, компостуванні в бурти, спалюванні посліду, анаеробному розкладанні компосту для отримання біогазу, вермикомпостуванні, спалюванні відходів для отримання теплової та електроенергії, термічній сушці посліду птахів на органічне добриво, проведенні піролізу, переробки посліду в установках методом біоферментації. Робота містить короткий опис патентів на винаходи і корисні моделі з сучасними підходами до технологій переробки посліду птахів. Птахофабрики все більше ускладнюють і без того непросту екологічну ситуацію, так як накопичуваний пташиний послід є суттєвим джерелом забруднення навколишнього середовища. Показана відсутність системного та екологічного підходу до вирішення проблеми переробки посліду птахів. В країні необхідні спеціалізовані підприємства з переробки і утилізації відходів птахівництва. EN: Utilization of bird droppings is one of the most pressing environmental problems in the agrarian world. Its solution is a priority task for agriculture. At the level with the manufacture of the main products (meat and eggs of poultry), waste is produced in large quantities at modern poultry complexes. The largest share among them belongs to the bird droppings. According to the State Statistics Service of Ukraine, the poultry population as of November 1, 2021 in farms of all categories is 226,932.2 thousand heads. Currently, there are 385 poultry breeding enterprises in Ukraine. Different in their capacity, they produce 8,785.6 million eggs and 1,628.6 thousand tons of meat annually. Poultry enterprises and households accumulate droppings on a daily basis. The processing of bird droppings has become a complex problem, since it requires money, the availability of storage areas for waste and agricultural land for the application of the obtained organic fertilizers, etc. The modern methods and technologies for recycling of bird droppings are presents in article. Each of these technologies has visible and hidden disadvantages. Poultry waste is used not ecologically and irrationally during storage in storages for droppings, drying droppings of various moisture content, composting into piles, burning droppings, anaerobic decomposition of compost for biogas production, vermicomposting, droppings incineration to obtain heat and electric energy, pyrolysis, and recycling of droppings in installations by biofermentation method. The work contains a brief description of patents for inventions and utility models with modern approaches to technologies for recycling bird droppings. Poultry farms are increasingly complicating the already difficult ecological situation, since the accumulated bird droppings is a significant source of environmental pollution. The absence of a systemic and ecological approach to solving the problem of recycling bird droppings is shown. The country needs specialized enterprises for the recycling and disposal of poultry waste. RU: В статье представлены современные способы и технологии переработки помета птиц. Каждая из приведенных технологий имеет видимые и скрытые недостатки. Отходы птицеводства используются неэкологично и нерационально при хранении в хранилищах для помета, сушке помета различной влажности, компостировании в бурты, сжигании помета, анаэробном разложении компоста для получения биогаза, вермикомпостировании, сжигании отходов для получения тепловой и электрической энергии, проведении пиролиза, переработки помета в установках методом биоферментации. Работа содержит краткое описание патентов на изобретения и полезные модели с современными подходами к технологиям переработки помета птиц. Птицефабрики все больше усложняют и без того непростую экологическую ситуацию, так как накапливаемый птичий помет является существенным источником загрязнения окружающей среды. Показано отсутствие системного и экологического подхода к решению проблемы переработки помета птиц. В стране необходимы специализированные предприятия по переработке и утилизации отходов птицеводства.
Modern patented methods for recycling of bird droppings
Современные запатентированные способы переработки помета птиц
Keywords: послід птахів; спосіб переробки; компостування; утилізація; розробка; патент; bird droppings; recycling method; composting; disposal; development; patent; помет птиц; способ переработки; компостирование; утилизация; разработка; патент